Bioactive compounds and advanced processing technology: Phaleria macrocarpa (sheﬀ.) Boerl, a review - Easmin, Mst. Sabina; Sarker, Md. Zaidul Islam; Ferdosh, Sahena; Shamsudin, Siti Hadijah; Yunus, Kamaruzzaman; Uddin, Md. Salim; Rahman, Md. Mokhlesur; Akanda, Md. Jahurul Haque; Hossain, Md. Sohrab; Khalil, HPS Abdul (Wiley Online Library, 2015)
Recent technological advances and the development of new methods has provided an opportunity to obtain highly purified natural bioactive compound extracts with potential for the treatment and prevention of human diseases. The use of hazardous and toxic solvents for the extraction and processing of bioactive compounds from plant materials is considered a problem for health, safety and environmental pollution. Advanced technology aims to increase production of the desired compounds and find an alternative to using toxic solvents in the extraction of bioactive compounds from plant materials. The ever growing interest in plant bioactive compounds and today’s concerns about environment issues have led to an increased need for an eﬃcient and green extraction method. This review is focused on the extraction of bioactive compounds from plants using advanced and environment-friendly methods such as supercritical fluid extraction, microwave-assisted extraction, ultrasound-assisted extraction and similar techniques that can extract rapidly and free from organic residues. An updated overview of the bioactive compounds present in the plant Phaleria macrocarpa and its extraction, fractionation, purification and isolation is provided. The advantages and disadvantages of both conventional and non-conventional extraction methods are also discussed in this review.